Existence of a Hydrogen Sulfide:Ferric Ion Oxidoreductase in Iron-Oxidizing Bacteria - Sugio, Tsuyoshi (1992)
The existence of a hydrogen sulfide:ferric ion oxidoreductase, which catalyzes the oxidation of elemental sulfur with ferric ions as an electron acceptor to produce ferrous and sulfite ions, was assayed with washed intact cells and cell extracts of various kinds of iron-oxidizing bacteria, such as Thiobacillus ferrooxidans 13598, 13661, 14119, 19859, 21834, 23270, and 33020 from the American Type Culture Collection, Leptospirillum ferrooxidans 2705 and 2391 from the Deutsche Sammlung von Mikroorganismen, L. ferrooxidans BKM-6-1339 and P3A, and moderately thermophilic iron-oxidizing bacterial strains BC1, TH3, and Alv. It was found that hydrogen sulfide:ferric ion oxidoreductase activity comparable to that of T. ferrooxidans AP19-3 was present in all iron-oxidizing bacteria tested, suggesting a wide distribution of this enzyme in iron-oxidizing bacteria.